INFLUENCE LEADERSHIP STYLE AND WORK DISCIPLINE TOWARDS WORK PERFORMANCE EMPLOYEES - Aspizain Caniago; Dharliana Dharliana (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This research was conducted to determine the influence of work discipline and leadership style on employee performance. The study was conducted at PDAM Tirta Griya Nata Cirebon with a total sample of 66 respondents. The determination of respondents selected through the Probability Sampling technique with the type of sample is Random Sampling. Probability sampling is a technique that provides an equal opportunity for each element (member) of a population to be selected as a member of the sample. The data analysis method uses validity, reliability, classical assumptions, regression analysis, as well as t-tests and F- tests processed through the IBM SPSS 23 (Special Package For Statistical Science) application. The results of the study partially showed that there was a significant positive influence of leadership style and work discipline on employee performance, simultaneously there was a significant positive influence of 27.5% between the variables of leadership style and work discipline on employee performance, and the rest was influenced by 72.5% by other factors. For PDAM Tirta Griya Nata Cirebon, it is important to pay attention to the leadership style given to employees and improve employee work discipline in order to create high employee performance and have a good impact on PDAM Tirta Griya Nata Cirebon